(untitled) (Nexo Revista Científica, 2021)
The utilization of unconventional technogenic raw materials in producing construction materials is a topical economic and environmental issue. The issue’s resolution is impeded by the fact that the overburden rocks of apatite nepheline deposits contain nepheline classified as a deleterious impurity for concrete aggregates under the current standards. This paper is aimed to conduct specialized tests of rocks, aggregates, and concretes for evaluating the corrosion resistance of these materials in water and acid media. The work involved using physical mechanical techniques as well as light and scanning microscopy. It is scientifically validated that nepheline aggregate included in concrete and behaving actively as related to calcium hydroxide produces a denser area of contact with the cement matrix, which favours an enhanced corrosion resistance of concrete. The paper’s information is scientifically and practically valuable for resolving the issue with recycling the mining waste of apatite nepheline deposits and utilizing their overburden rocks as concrete aggregates.